2004
DOI: 10.1080/0266476042000285503
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Process Mean and Variability with One Non-central Chi-square Chart

Abstract: Traditionally, an X-chart is used to control the process mean and an R-chart to control the process variance. However, these charts are not sensitive to small changes in process parameters. A good alternative to these charts is the exponentially weighted moving average (EWMA) control chart for controlling the process mean and variability, which is very effective in detecting small process disturbances. In this paper, we propose a single chart that is based on the non-central chi-square statistic, which is more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 20 publications
0
35
0
1
Order By: Relevance
“…Most of the current research has been focused on the Hotelling's T 2 control chart and the multivariate EWMA control chart for controlling the process mean. Yeh et al 16 , Surtihadi et al 17 , Cheng and Thaga 18 and Costa and Rahim 19 propose and study multivariate EWMA and CUSUM control charts to control the dispersion of a multivariate process. As stated before univariate control charts for autocorrelated processes have been discussed in the literature (Montgomery 1 , Box and Luceñno 2 ), however, for multivariate processes the general focus has been placed to uncorrelated processes.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the current research has been focused on the Hotelling's T 2 control chart and the multivariate EWMA control chart for controlling the process mean. Yeh et al 16 , Surtihadi et al 17 , Cheng and Thaga 18 and Costa and Rahim 19 propose and study multivariate EWMA and CUSUM control charts to control the dispersion of a multivariate process. As stated before univariate control charts for autocorrelated processes have been discussed in the literature (Montgomery 1 , Box and Luceñno 2 ), however, for multivariate processes the general focus has been placed to uncorrelated processes.…”
Section: Introductionmentioning
confidence: 99%
“…Costa and Rahim 9 showed that this control chart can effectively detect the changes in mean and variance including the decrease in variance. Note that there are three parameters, d 0 , d 1 and L, involved in the testing statistics and there is no exact way to specify them to achieve some nearly 'optimal' performance.…”
Section: Existing Workmentioning
confidence: 98%
“…Other statistical tools that assists with the quantification and management of variability/heterogeneity not discussed in this paper include chi-square and R charts (Duncan, 1956;Harris and Ross, 1991;Costa and Rahim, 2004;Woodall and Spitzner, 2004). These charts have been extensively used with great success for statistical quality control in the manufacturing and chemical industries.…”
Section: Testing For Heterogeneity In Complex Mining Environmentsmentioning
confidence: 99%